Acute Effects of the New Method Sarcoplasma Stimulating Training Versus Traditional Resistance Training on Total Training Volume, Lactate and Muscle Thickness - de Almeida, Fernando Noronha; Lopes, Charles Ricardo; Conceição, Raphael Machado da; Oenning, Luan; Crisp, Alex Harley; de Sousa, Nuno Manuel Frade; Trindade, Thiago Barbosa; Willardson, Jeffrey M.; Prestes, Jonato (Frontiers in Physiology, 2019)
Background: Trained subjects have difficulty in achieving continued results following years of training, and the manipulation of training variables through advanced resistance training (RT) methods is widely recommended to break through plateaus. Objective: The purpose of the present study was to compare the acute effects of traditional RT (TRT) versus two types of the sarcoplasma stimulating training (SST) method on total training volume (TTV), lactate and muscle thickness (MT). Methods: Twelve trained males (20.75 ± 2.3 years; 1.76 ± 0.14 m; body mass = 79.41 ± 4.6 kg; RT experience = 4.1 ± 1.8 years) completed three RT protocols with a randomly sequenced order: TRT, SST contraction type (SST-CT), or SST rest interval variable (SST-RIV) with seven days between trials in arm curl (elbow flexors), and triceps pulley extension (elbow extensors) performed in the same day. Results: The SST groups displayed greater acute biceps, and triceps brachii MT versus the TRT session, with no difference in lactate levels between them. The SST-CT resulted in greater biceps, and triceps brachii MT versus the SST-RIV session. The TTV was greater for the TRT session versus SST sessions; except in the case of the elbow flexors (no difference between TRT and SST-CT), and higher for SST-CT versus the SST-RIV. Conclusion: Trained subjects may benefit from using the SST method, as this method may offer a superior muscle thickness stimulus, and reduced training time, even with a lower TTV.